The needs of mothers to newborns hospitalised in intensive care units - Sikorova, Lucie; Kucova, Jana (Biomedical papers, 2012)
Objective: The aim of the survey was to identify the needs of mothers to infants hospitalized in intensive care units (ICUs) and second, to assess the level of parental support provided by the health personnel.Methods: The sample consisted of 147 mothers to infants hospitalized in ICUs. The research was conducted over six months in ICUs for newborns at two hospitals in Ostrava. The study used two standardized questionnaires: The parental stressor questionnaire scale: Neonatal Intensive Care Unit which measures the degree of stress in parents of hospitalized infants and the questionnaire The Nurse Parent Support Tool which evaluates the level of parental support provided by nursing staff.Results: The highest level of stress was identified in the parental role. Specifically, the inability to help the child remain separate from the mother, a feeling of helplessness and inability to protect the child from painful procedures and the inability to feed her baby. Mothers evaluated the support of nursing staff in most of these areas as high. Top were rated the ability of the caring staff to respond well to the questions of parents and the mother's willingness to engage in childcare.Conclusion: Intensive care units for the newborn obviously need to be family-centered care and at the same time they must be aware of all the factors that can be sources of stress for the parents.Only in this way can stress be eliminated with positive impact on the relationship between mother and child.
Keywords: parental stressor scale; neonatal intensive care unit; the nurse parent support tool; stress